"Features of Far North Life Pictured by the Bartlett-Academy of Natural Sciences Greenland Expedition" (Philadelphia Evening Bulletin, 1930)
"In addition to collecting natural history specimens for the Academy, the expedition, in command of Captain Robert Bartlett, skipper of Admiral Peary's Roosevelt, made a study of the Eskimos of Clavering Island. An Eskimo house on the island is shown after being uncovered by the expedition. Mr. Whitney also was with Admiral Peary in the Arctic." With clipping